Digital Marketing and Lifestyle Changes in Thai Society - Yotkaew, Pramote (Journal of Multidisciplinary Academic Research and Development (JMARD), 2021)
This paper aims to explain how the transformation of digital marketing affects a new way of life in Thai society. Based on marketing and technological theory, the problem of media’s data integration was analyzed. Additionally, the researcher interprets, based on social reality, adoption of advancing with a new era of life. Due to the crisis, a new way of life, known as “New Normal”, has emerged in Thai society. The “New Normal” changes our usual behavior. People have to keep social distancing and many of them turn to pay more attention to their health. Also, the behavior of purchasing products and investments has changed. Moreover, people are going online increasingly such as using social media and other platforms. Thus, marketing has to be changed in response to this new way of life. It has changed from traditional marketing, which focuses on the 4Ps concept, to digital marketing with the 4Es concept. New marketing meets human needs in the form of comfort, impression, and good participation in the organization. This concept will enable the organization to survive in the transition to a new way of life. According to Buddhist principles, adaptation requires consciousness. That is, we have to know our own shortcomings and then fix them. Additionally, we have to work on improving, transforming ourselves until becoming acquainted with those good things. Following Patan 4 principle (Effort 4), we have to rely on ourselves, stop doing bad things, do things that we never did, and always do good things for happily living in a new way of life.